Restored riverine wetlands in a headwater stream can simultaneously behave as sinks of N2O and hotspots of CH4 production. (1st September 2021) - Zhang, Wangshou; Li, Hengpeng; Pueppke, Steven G.; Pang, Jiaping
Abstract: Wetlands can improve water quality, but they are also recognized as important sources of greenhouse gases (GHG) such as nitrous oxide (N2 O) and methane (CH4 ). Emissions of these gases from wetland ecosystems, especially those in headwaters, are poorly understood. Here, we determined monthly concentrations of dissolved N2 O and CH4 in a headwater stream of the Taihu Lake basin of China that contains both wetland and non-wetland reaches. Daily GHG dynamics in the wetland reach were also investigated. Riverine N2 O and CH4 concentrations generally varied within 10–30 nmol L −1 and 0.1–1.5 μmol L −1, respectively. CH4 saturation levels in the wetland reach were about seven times higher than those in the non-wetland reach, but there was no difference in N2 O saturation. In the wetland reach, saturation levels of CH4 peaked in July, coincident with a dip in N2 O saturation to levels below its saturated solubility. This underscores that hotspots of CH4 production and sinks for N2 O can occur occasionally in wetlands in mid-summer, when vegetative growth and microbial activities are high. Diurnal measurements indicated that CH4 saturation in water flows passing through the wetlands from midnight through the early morning can surge to levels 10 times higher than those detected at other times of the day. Simultaneously, saturation levels of N2 O decreased by 75%, indicating a net consumption of N2 O. Changes in nutrient supply determined by upstream inflows, as well as dissolved oxygen, pH, and other environmental factors mediated by the wetlands, correlate with the differentiated behavior of N2 O and CH4 production in wetlands. Additional work will be necessary to confirm the roles of these factors in regulating GHG emissions in riverine wetlands. Graphical abstract: Image 1 Highlights: GHG concentrations in both wetland and non-wetland reaches varied daily and monthly. Sinks for N2 O and hotspots of CH4 production occasionally occur in wetlands. The presence of riverine wetlands altered N2 O and CH4 production. Abstract : (i) GHG concentrations in both wetland and non-wetland reaches varied daily and monthly; (ii) Wetlands can be simultaneous sinks of N2 O and sources of CH4 ; (iii) Riverine environmental conditions mediated by wetlands are responsible for differentiated behaviors of N2 O and CH4 production.